The Influence of Experience, Supervision and Auditor Independence on Performance Audit - Asriani, Linda; Yulisfan; Faurini, Novi; Syari, Meilya Evita; Fachri, Fadhlan; Zebua, Totona Berkat Elsuran (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of experience, supervision, and independence of internal auditors on performance audits. Performance audits are systematic evaluations of the effectiveness, efficiency, and economy of an organization in achieving its goals. Internal auditors play an important role in providing added value through quality performance audits. The research method used is a quantitative approach with a descriptive associative research type. The population and this research are 32 universities in Medan City which have 32 internal auditors (LAPM), where the data collection technique is carried out by observation studies, distributing questionnaires to 32 universities in Medan City, and documentation studies. The data analysis technique uses multiple linear regression with the help of SPSS software. The results of the study indicate that the auditor independence variable has a significant effect on performance audits, while experience and supervision do not show a significant effect. This indicates that although experience and supervision are important, the auditor's objectivity and freedom in carrying out tasks are key factors in improving the quality of performance audits. This finding is expected to be an evaluation material for organizational leaders in strengthening the internal audit function through increasing independence and continuous coaching. This research also contributes to the development of performance audit literature, especially in higher education in Medan City